1995
DOI: 10.1007/bf02300971
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia crystals with yttrium and cerium oxides

Abstract: Results obtained for a new material, namely, zirconia crystals stabilized by Y203 and CeO2 and containing a technological addition of neodymium oxide, tested at room temperature are described. Special features of the surfaces of the crystal blocks grown and the distribution of the additions introduced into the charge over their height are investigated. The dependences of the amounts of the stabilizing components and the fracture properties of the investigated material on its strength are determined. Certificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
1
0
3
Order By: Relevance
“…14) In the case of yellow, BaO and Fe 2 O 3 were confirmed to act as a coloring element. These elements were in agreement with the coloring elements for yellow color reported by Guo et al 15) On the other hand, CeO 2 and Ho 2 O 3 were confirmed to act as a coloring element for red, 16) and Co 2 O 3 and Fe 2 O 3 were contained as a coloring element for purple. In the case of colorless, however, trace amounts of Cr 2 O 3 and TiO 2 were contained in addition to Y 2 O 3 and HfO 2 the essential components of CZs without affecting colors.…”
Section: Resultssupporting
confidence: 90%
“…14) In the case of yellow, BaO and Fe 2 O 3 were confirmed to act as a coloring element. These elements were in agreement with the coloring elements for yellow color reported by Guo et al 15) On the other hand, CeO 2 and Ho 2 O 3 were confirmed to act as a coloring element for red, 16) and Co 2 O 3 and Fe 2 O 3 were contained as a coloring element for purple. In the case of colorless, however, trace amounts of Cr 2 O 3 and TiO 2 were contained in addition to Y 2 O 3 and HfO 2 the essential components of CZs without affecting colors.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, for ZrO 2 materials having Z = 1, the coefficients presented in Table 3 are preferable. Note that M and N are approximately equal for ceramics and crystals of the PSZ type (eft 3Y-Ce-PSZ-K with 0.3% CeO2 [31]), which makes it possible to evaluate their crack resistance using one equation with coefficients averaged by the leastsquares method).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Результаты исследования механических свойств кри-сталлов ЧСЦ, солегированных оксидами иттрия и церия приведены в работах [10,11]. Так, в работе [10] …”
Section: Introductionunclassified